Sequestration of the abeta Peptide prevents toxicity and promotes degradation in vivo. - Luheshi, L.M.; Hoyer, W.; de Barros, T.P.; van Dijk Härd, I.; Brorsson, A.C.; Macao, B.; Persson, C.; Crowther, D.C.; Lomas, D.A.; Ståhl, S.; Dobson, C.M.; Härd, T. (PLoS Biology, 2010)
Protein aggregation, arising from the failure of the cell to regulate the synthesis or degradation of aggregation-prone proteins, underlies many neurodegenerative disorders. However, the balance between the synthesis, clearance, and assembly of misfolded proteins into neurotoxic aggregates remains poorly understood. Here we study the effects of modulating this balance for the amyloid-beta (Abeta) peptide by using a small engineered binding protein (Z(Abeta3)) that binds with nanomolar affinity to Abeta, completely sequestering the aggregation-prone regions of the peptide and preventing its aggregation. Co-expression of Z(Abeta3) in the brains of Drosophila melanogaster expressing either Abeta(42) or the aggressive familial associated E22G variant of Abeta(42) abolishes their neurotoxic effects. Biochemical analysis indicates that monomer Abeta binding results in degradation of the peptide in vivo. Complementary biophysical studies emphasize the dynamic nature of Abeta aggregation and reveal that Z(Abeta3) not only inhibits the initial association of Abeta monomers into oligomers or fibrils, but also dissociates pre-formed oligomeric aggregates and, although very slowly, amyloid fibrils. Toxic effects of peptide aggregation in vivo can therefore be eliminated by sequestration of hydrophobic regions in monomeric peptides, even when these are extremely aggregation prone. Our studies also underline how a combination of in vivo and in vitro experiments provide mechanistic insight with regard to the relationship between protein aggregation and clearance and show that engineered binding proteins may provide powerful tools with which to address the physiological and pathological consequences of protein aggregation.